Effects of Human Activity on the Fallen-Fruit Foraging Behavior of Carnivoran Species in an Urban Forest - Osugi, Shigeru; Trentin, Bruna Elisa [UNESP]; Koike, Shinsuke (Mammalogical Society of Japan, 2022)
The purpose of the present study was to determine whether and how the fruit-foraging behaviors of two frugivorous carnivorans, the raccoon dog (Nyctereutes procyonoides) and Japanese badger (Meles anakuma), are influenced by the presence of humans. In the first investigation, we contrasted the frequency and duration of foraging visits to fruit-bearing trees in an urban forest and a mountain forest. In the second investigation, we employed a modeling approach to ascertain whether the degree of shelter affected tree selection in the urban forest by these frugivorous species. The results of the first investigation showed that both species foraged almost solely at night in the urban forest and had significantly shorter visit times in the urban forest than in the mountain forest. The second investigation revealed that both species selected to forage in sheltered places where the forest floor was covered with vegetation. We found that fruit production did not affect tree choice in these places, indicating that the mammals prioritize avoiding humans over effective foraging in places with more plentiful fruits. These tendencies to forage at night and in areas with adequate shelter indicate that these species have adapted their behaviors to avoid humans in urban environments.
Keywords: Aphananthe aspera; Daily activity; Food habits; Ginkgo biloba; Nocturnal